Kompas 4 : Westkust USA. - Leering, Jean; Thiemann, Eugen; Zdenek, Felix; Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum Eindhoven, 1969)
Bell, Larry ; Bengston, Billy Al ; Conner, Bruce ; Diebenkorn, Richard ; Irwin, Robert ; Kauffmann, Craig ; Kienholz, Edward ; Lobdell, Frank ; Mason, John ; McCracken, John ; Nauman, Bruce ; Price, Kenneth ; Ruscha, Ed ; Smith, Hassel ; Still, Clyfford ; Thiebaud, Wayne ; Voulkos, Peter ; Wheeler, Doug ; Wiley, William T.
bibliog. p. 50
biog., ind. tent., gr. tent. p. 39-47
Engels
Nederlands
Kompas 4 : Westkust USA / West Coast USA, Van Abbemuseum Eindhoven, 21 november 1969 tm 4 januari 1970
boek
Keywords: jaren 60; U.S.A.